Innovation and Technology Management in Modern Enterprises - Yayha, Mohammed AbulJaber; Samoea, Rafaa Faraj; Abedah, Maher; Fahmi, Ahmed Mohammed; Temnikov, Volodymyr (Journal of Ecohumanism, 2024)
Background: Innovation and technology management are crucial for contemporary businesses' profitability and long-term sustainability. Due to rapid technological advancements and a volatile business environment, companies must adapt and utilise innovation to maintain competitiveness and relevance. This article explores the various aspects of innovation and technology management in modern businesses. Objective: The primary aim of this study is to scrutinize the strategies and approaches implemented by contemporary enterprises to foster innovation and streamline technology management. The investigation aims to identify crucial factors that facilitate or impede innovation and technology management, thereby contributing to a better understanding of the present-day corporate landscape. Methodology: To gain insight into the contemporary approaches to innovation and technology management in organisations, this study conducts a thorough review of existing literature, case studies, and surveys across various industries. The acquired data undergo qualitative and quantitative analysis to offer a comprehensive perspective. The research findings are as follows: Results: Effective integration of internal and external sources, fostering an innovative culture, and strategic alignment with organizational goals are key factors for successful technology and innovation management in modern businesses. Additionally, leadership is critical in encouraging innovation and creating a supportive environment. The significance of these factors cannot be overstated. Conclusion: The conclusion of this article highlights the important role that technology management and innovation have in the success of modern businesses. Organisations must comprehend the fundamental principles and strategies that allow for effective technology management and innovation to ensure long-term growth and sustainability in an ever-competitive global market. This knowledge is a valuable resource for business leaders, lawmakers, and academic navigating the complexities of the contemporary business industry.